The Relationship of Aspects of Identity, Awareness of Brain-Friendly Instruction and Language Skills: A Correlational Study - AbdolHamid Mohammadi; Ayatollajh Razmjoo; Shahram Afraz; Fazlolah Samimi (Iranian Evolutionary Educational Psychology Journal)
Objective: The main objective of this study is to explore the relationship between different aspects of identity, awareness of brain-friendly instruction (BFI), and language skills (Reading and Speaking) among Iranian psychology students. Methods: The study included 100 male and female students aged 18 to 30, who were attending English classes. To assess the various aspects of identity in psychology students, the researchers utilized the fourth version of Aspects of Identity Questionnaire (AIQ-IV) (Cheek, Smith, and Tropp, 2002). This questionnaire consists of 45 items, measuring five aspects of identity: Personal (10 items), relational identity (10 items), social identity (7 items), collective (8 items), and special items (10 items). Additionally, the researchers assessed the awareness of brain-friendly instruction using Brain-Friendly Teaching Inventory developed by Sattari Gavareshk & Tabatabaee-Yazdi (2021). After completing the questionnaires, the participants were scheduled for reading and speaking tests. Results: 2021). After completing the questionnaires, the participants were scheduled for reading and speaking tests. The study's findings revealed that social identity and motivation (a component of awareness of brain-friendly instructions) were the most significant predictors of psychology students' speaking performance. Furthermore, motivation and personal identity were identified as the strongest predictors of reading performance among psychology students. Conclusions: These findings hold significant implications for language teachers and individuals planning to take preparation courses for the IELTS examination.